KANDUNGAN UNSUR HARA MAGNESIUM PADA PETAK UKUR PERMANEN DENGAN BERBAGAI TIPE PENUTUPAN VEGETASI DI HUTAN PENDIDIKAN WANAGAMA I GUNUNGKIDUL - , FIERDAZ SABDA A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest Education Wanagama I formerly was a critical area of the arid and barren with a tread condition which is stony ground. Development and management is carried out by planting various kinds of vegetation topographic variations, variation of geological and soil karakteristik different, for it is need for thorough monitoring. One form of such monitoring is about the characteristics of soil chemical elements by making the Permanent Sample Plots (PSP) in several locations in the area of forest Education Wanagama I Gunungkidul. One of the nutrient elements content analysis can be carried out, namely the analysis of the content of Magnesium (Mg). The purpose of research to knowing the value of the content of Magnesium (Mg) in the PUP with various types of closure of the vegetation suffered no tillage in Forest Education Wanagama 1 Gunungkidul. Research conducted at the Permanent Sample Plots (PSP) Forest Education Wanagama I Gunungkidul acreage crop Teak (Plots of 6 and 7), Mahoni (Plots of 14) Legaran (Plots of 18) Kiputri, Gliriside, Ebony, and Cendana (Plots of 5). Data collection is done by making observations and taking soil samples. Analysis of soil samples is performed in the laboratory of soil science in the Faculty of Forestry of GADJAH MADA UNIVERSITY. The Magnesium content of value analysis results are analyzed in the form of tables and charts to be described in accordance with the differences in the depth of the soil. From the results of observation of the levels of the element Magnesium Swath of land in Permanent Sample Plots (PSP) Forest Education Wanagama I Gunungkidul acreage crop Teak (Plots of 6 and 7), Mahoni (Plots of 14) Legaran (Plots of 18) Kiputri, Gliriside, Ebony, and Cendana (Plots of 5) included in the very low criteria where the results < 0.3 me/100gr. Magnesium nutrient Levels in each of the stands in the forest of 0.030 Gliriside me/100 gr, Legaran of 0,029, me/100 gr soil, Ebony of 0,029 me/100 gr soil, Jati of 0.030 me/100 gr soil, Jati of 0,029 me/100 gr soil, mahogany of 0,029 me/100 gr soil, Kiputri of 0,029 me/100 gr soil, Cendana of 0.030 me/100 gr soil. Need for Magnesium nutrient management to increase the productivity of the land.